2000
DOI: 10.1034/j.1399-3011.2000.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic control of the relative yield of the deamidation of asparagine and isomerization of aspartic acid residues

Abstract: Selective deamidation of Asn67 of RNase A to beta-Asp67 and Asp67 residues at neutral pH initially produces greater amounts of the beta-Asp derivative. As the reaction proceeds the relative concentration of [Asp67]-RNase A increases and, at equilibrium, becomes predominant. Such a discrepancy between the kinetic and thermodynamic control on reaction products is discussed in light of information from X-ray three-dimensional analysis and the lower thermodynamic stability of the beta-Asp derivative relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…This calculation showed that 1.1-1.8 Asp/Asn residues were racemised per polypeptide in a 70-year-old person (Table 1). This factor alone is likely to lead to significant protein denaturation, especially since the process which leads to racemisation of Asp via a cyclic intermediate can also generate three isoaspartyl residues for each altered Asp residue (Capasso and Di Cerbo 2000). The values shown in Table 1 illustrate the quantitative importance of this process for the aged lens; however, it should be noted that different proteins, and regions within them, very likely behave differently in terms of their susceptibility to racemisation, so the values must be considered as estimates only.…”
Section: Discussionmentioning
confidence: 99%
“…This calculation showed that 1.1-1.8 Asp/Asn residues were racemised per polypeptide in a 70-year-old person (Table 1). This factor alone is likely to lead to significant protein denaturation, especially since the process which leads to racemisation of Asp via a cyclic intermediate can also generate three isoaspartyl residues for each altered Asp residue (Capasso and Di Cerbo 2000). The values shown in Table 1 illustrate the quantitative importance of this process for the aged lens; however, it should be noted that different proteins, and regions within them, very likely behave differently in terms of their susceptibility to racemisation, so the values must be considered as estimates only.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The relative proportions of aspartyl to isoaspartyl products is under kinetic and thermodynamic control. 17 Based on a large number of model pentapeptide deamidation kinetics, it is well understood that the rate of deamidation of asparagine is significantly determined by the neighbouring amino acids especially the carboxyl side (n11) amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive methods utilize the enzyme protein isoaspartyl methyl transferase (PIMT) to selectively methylate isoAsp residues in peptides and proteins with isotopically labeled methyl groups, thus detecting deamidation, but not localizing the site or determining the relative abundance of the products [24,25]. Separation of proteins from their deamidated counterparts can be done by ion-exchange HPLC [23,26,27] or IEF gel electrophoresis [14,28] because there is a net change in the isoelectric point with deamidation. However, the methods are not used for differentiation and relative quantitation of the deamidation products because the acidity constants of the isomers are so similar; isoAsp and Asp were shown to have a difference of only 0.7 pK a units [17].…”
mentioning
confidence: 99%
“…Hydrolysis of the succinimide intermediate in linear peptides typically results in an approximate 3:1 ratio of products favoring the isoAsp form [15][16][17][18][19][20][21], but ratios from succinimide hydrolysis within a structurally restricted environment, such as within a protein's tertiary structure, can deviate from this ratio [22]. For example, N67 of ribonuclease A ultimately deamidated to a 3:2 ratio in favor of the Asp form due to the restricted flexibility of the region by two flanking disulfide bonds [23]. Therefore, a method that determines the relative abundance of the products is necessary for complete characterization of asparaginyl deamidation and Asp isomerization that is suspected to affect a protein's structure and function.…”
mentioning
confidence: 99%